2016
DOI: 10.1016/j.ajhg.2016.09.019
|View full text |Cite|
|
Sign up to set email alerts
|

Biallelic Loss of Proprioception-Related PIEZO2 Causes Muscular Atrophy with Perinatal Respiratory Distress, Arthrogryposis, and Scoliosis

Abstract: We report ten individuals of four independent consanguineous families from Turkey, India, Libya, and Pakistan with a variable clinical phenotype that comprises arthrogryposis, spontaneously resolving respiratory insufficiency at birth, muscular atrophy predominantly of the distal lower limbs, scoliosis, and mild distal sensory involvement. Using whole-exome sequencing, SNPchip-based linkage analysis, DNA microarray, and Sanger sequencing, we identified three independent homozygous frameshift mutations and a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 35 publications
2
44
0
1
Order By: Relevance
“…Our mouse genetics data demonstrate that Piezo2 is a versatile mechanotransducer, functioning as a sensor of lung inflation in addition to touch and proprioception 15,17 . Recently, humans carrying compound inactivating variants of PIEZO2 were reported to have selective loss of discriminative touch perception and profoundly decreased proprioception; these individuals also exhibited shallow breathing during infancy 35,36 . Thus, the general role of Piezo2 in somatosensory mechanotransduction is conserved between mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Our mouse genetics data demonstrate that Piezo2 is a versatile mechanotransducer, functioning as a sensor of lung inflation in addition to touch and proprioception 15,17 . Recently, humans carrying compound inactivating variants of PIEZO2 were reported to have selective loss of discriminative touch perception and profoundly decreased proprioception; these individuals also exhibited shallow breathing during infancy 35,36 . Thus, the general role of Piezo2 in somatosensory mechanotransduction is conserved between mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Distal arthrogryposis in patients with DAIPT has been observed as "congenital," particularly regarding bilateral foot deformities [Delle Vedove et al, 2016]. Contracture deformities of the upper limbs were present in 15 of the 16 previously reported patients.…”
Section: Discussionmentioning
confidence: 71%
“…Cognitive development was usually normal. Only in one family, mild cognitive disability had been described in 2 affected children, possibly influenced also by a low socioeconomic status of the family [Delle Vedove et al, 2016]. Heterozygous carriers of PIEZO2 loss-of-function mutations (parents and siblings) were healthy, without any signs of neuromuscular or skeletal symptomatology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although Piezo2 knockout is perinatal lethal in mice, human life expectancy is normal. It has been suggested that humans with homozygous loss-of-function alleles may produce some functional PIEZO2 through alternative splicing 44. This may explain the relatively mild phenotype compared with mice.…”
Section: Genes Encoding Components Of the Peripheral Nervous Systemmentioning
confidence: 99%